Kebocoran Data Publik Dan Etika Ti Dalam Tata Kelola Serta Resiliensi Siber BPJS-PDN 2024 - Khalidah, Audita Najwa; Ragil, Ragil; Yudianto, Raka Prabu Wikrama; Saputra, Dylan; Tramajie, Mugi Sugiharto; Yunita, Yunita (Universitas Pakuan, 2026)
Public Data Leakage and IT Ethics in Cyber Governance and Resilience BPJS-PDN 2024 Digital transformation in Indonesia’s public service sector faces significant challenges related to data security and IT professional ethics. This study compares cybersecurity governance and cyber resilience in two major public data breach incidents: BPJS Kesehatan (2021) and the National Data Center/PDN (2024), while examining the application of IT professional ethics. Using a qualitative comparative approach through literature review of official reports and scientific publications from the last five years, the findings show shared weaknesses in both incidents, including limited backup systems, weak vendor oversight, and low ethical awareness. BPJS Kesehatan demonstrates stronger governance and better coordination with the National Cyber and Crypto Agency (BSSN), whereas PDN shows weak mitigation efforts and limited public accountability. The study concludes that strengthening IT professional ethics, improving cybersecurity governance, and establishing an independent oversight body to ensure consistent implementation of the Personal Data Protection Law are essential for enhancing national cyber resilience.